Sampling of environmental electromagnetic frequencies demonstrates the evolution of the nervous system toward social cognitive reflexes - Hazani, Joseph A. (Frontiers in Computational Neuroscience, 2023)
The aim of this research is to help inspect the motion of cell life by applying electrical engineering scientific techniques to the cellular evolution of human neural networks. Using a mathematically rigorous theory of cellular biological progression, the hypothesis will demonstrate that cell life evolves toward increasing the organism's resonant energy transfer or “exposing points” with its natural environment. This increases the sampling points of electromagnetic radiation frequencies available for transferal into its biological system to stabilize its cellular reproduction cycle as a function of physical motion measurable in volt-ampere or calories/second as an experimental measure of fitness.